Legal Protection for Victims of Cyber-Fraud - Wau, Glorianus; Panggabean, Mompang Lycurgus (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Online fraud cases are increasingly prevalent and represent a significant societal challenge. The diversity of these fraudulent activities indicates a lack of public vigilance and a high level of trust in information circulating on social media. This issue necessitates a robust legal framework to effectively safeguard victims within the rapidly evolving digital landscape. Purposes of the Research: he purpose of this study is to examine the legal protection mechanisms for victims of online fraud. It evaluates the limitations of the current legal system, which often prioritizes punishing perpetrators without an adequate focus on victim rehabilitation or the recovery of material losses caused by the various fraudulent activities in Indonesia. Methods of the Research: This research utilizes a normative legal research method, commonly referred to as doctrinal research, focusing on the analysis of online fraud cases. This approach is chosen because current criminal enforcement often lacks optimization in addressing victim needs, emphasizing punitive sanctions rather than comprehensive restitution for the actual harm and trauma suffered. Findings of the Research: The findings reveal that legal protection for victims is categorized into preventive and repressive measures. Repressive protection is essential, particularly through restitution to compensate for material losses. This study also confirms that current countermeasures align with Article 28 and Article 45A of Law Number 1 of 2024 regarding Electronic Information and Transactions.